2020
DOI: 10.3390/ijms21124198
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Involvement in DNA Oxidative Damage of Human Sperm Nuclear Basic Proteins of Healthy Young Men Living in Polluted Areas

Abstract: DNA oxidative damage is one of the main concerns being implicated in severe cell alterations, promoting different types of human disorders and diseases. For their characteristics, male gametes are the most sensitive cells to the accumulation of damaged DNA. We have recently reported the relevance of arginine residues in the Cu(II)-induced DNA breakage of sperm H1 histones. In this work, we have extended our previous findings investigating the involvement of human sperm nuclear basic proteins on DNA oxidative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 65 publications
0
77
0
1
Order By: Relevance
“…GSK-3 may also contribute to identifying markers for DNA damage since its substrates are regulated via the PI3K-AKT-GSK-3 ( Figure 4 b) signaling network [ 39 ]. In fact, DNA integrity analysis is a better diagnostic and prognostic marker of sperm reproductive potential, for example, changes in nuclear basic proteins in human sperm exposure to heavy metals were recently explored [ 40 ] to link to DNA damage. The current study aimed to explore translational protein markers specific to the process of capacitation to mimic sperm cells passing to the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 may also contribute to identifying markers for DNA damage since its substrates are regulated via the PI3K-AKT-GSK-3 ( Figure 4 b) signaling network [ 39 ]. In fact, DNA integrity analysis is a better diagnostic and prognostic marker of sperm reproductive potential, for example, changes in nuclear basic proteins in human sperm exposure to heavy metals were recently explored [ 40 ] to link to DNA damage. The current study aimed to explore translational protein markers specific to the process of capacitation to mimic sperm cells passing to the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs are very important to convert chromatin states and transition histones-protamines in human spermatozoa. GasPhos could be used to study the effects of heavy metals that lead to alterations in the reproductive health of marine organisms and humans [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, sperm cells are highly sensitive to the pro-oxidant effects of environmental pollutants, due to the limited volume of the cytoplasmic space, with less antioxidant defence, and sperm membrane lipids are target of ROS 57 . In this regard, we recently reported that male gametes are the most sensitive cells to the accumulation of damaged DNA and showed, through molecular investigations, that the sperm nuclear basic proteins from samples of men living in polluted areas have a new and unexpected behaviour, resulting involved in DNA oxidative damage 58 . The COVID-19 CFR map of the most important outbreaks in the world areas presenting, in recent decades, a negative trend in sperm quality, together with the average annual levels of PM 10 , PM 2.5 and NO 2 , shows a certain overlapping (figure 1).…”
Section: Sperm Decline In Polluted Areasmentioning
confidence: 99%